Multidisciplinary study of human remains from the 3rd century mass grave in the Roman city of Mursa, Croatia - Mario Novak; Orhan Efe Yavuz; Mario Carić; Slavica Filipović; Cosimo Posth (PLoS ONE, 2025)
During excavations in 2011, a peculiar archaeological feature representing a mass grave with seven completely preserved skeletons was discovered at the site of the Roman period city of Mursa (modern-day Osijek, Croatia). The archaeological context and direct radiocarbon dating indicate that the bodies were interred during the mid-3rd century CE. Bioarchaeological analysis shows that all seven individuals are adult males exhibiting numerous pathological lesions (e.g., enthesopathies, injuries). Carbon and nitrogen stable isotopes analysis indicates they had a mixed C3/C4-based vegetal diet with limited amounts of terrestrial animal protein and a very limited marine protein consumption. Ancient DNA analysis shows that individuals from the Mursa mass grave had a heterogenous ancestry. None of them show genetic continuity with the preceding local Early Iron Age population. The presented multidisciplinary analyses of the Mursa mass grave strongly suggest that the studied individuals were Roman soldiers, victims of a catastrophic event occurring as the result of the ‘Crisis of the Third Century’, most probably the battle of Mursa from 260 CE.